2018
DOI: 10.1063/1.5009817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blockage, arrangement, and channel dynamics on performance of turbines in a tidal array

Abstract: The performance and economics of turbines in a tidal array are largely dependent on the power per turbine, and so approaches that can increase this power are crucial for the development of tidal energy. In this paper, we combine a two-scale partial array model and a one-dimensional channel model to investigate the effects of blockage, turbine arrangement, and channel dynamics on tidal turbines. The power per arXiv:1711.00364v3 [physics.flu-dyn]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Otherwise, even in steady flow, the reference velocity u 1 that is used to calculate C P,Betz is influenced by the array operation and design, as shown in section IV. Thus maximising C P,Betz does not necessarily led to P T,max , when the assumption of unaltered flow is changed to head-driven flow for a further investigation, as shown in [21], [22]. This was avoided in model (IV) and (V) by using the unaltered (flow without the array) flow velocity u 0 instead of u 1 as energy reference to calculate the Betz coefficient of performance and P avail .…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, even in steady flow, the reference velocity u 1 that is used to calculate C P,Betz is influenced by the array operation and design, as shown in section IV. Thus maximising C P,Betz does not necessarily led to P T,max , when the assumption of unaltered flow is changed to head-driven flow for a further investigation, as shown in [21], [22]. This was avoided in model (IV) and (V) by using the unaltered (flow without the array) flow velocity u 0 instead of u 1 as energy reference to calculate the Betz coefficient of performance and P avail .…”
Section: B Discussionmentioning
confidence: 99%
“…Therefore optimal coefficient of performance does not necessarily lead to optimal operation in terms of maximized power output. This was shown by [21], [22] and is highly misleading for developers.…”
Section: B Reference Energy Scale In Tidal Channelsmentioning
confidence: 98%
“…On the other hand, water surface waves, combined with the turbulent wake flow from the upstream turbines and the local unsteadiness of the stream current, may produce a series of negative impacts, such as the inflow turbulence, dynamic structural loading and the variations in the hydrodynamics of flow–structure interaction and the performance of the turbine output. These influences have been investigated by theoretical [69], experimental [1015] and physical oceanography studies [16,17].
Figure 1Schematic of the blockage effect of a tidal turbine in an open channel flow.
…”
Section: Introductionmentioning
confidence: 99%
“…The global blockage ratio is then defined as B G = B A B L (= nπd 2 /4hw), where w is the channel width and B A is the array blockage, which represents the ratio between the cross-sectional areas of the array, hn(d +s), and the channel, hw. Willden et al [29] and Gong et al [30] have also sought to combine two-scale theory with the simple channel model of Garrett and Cummins [7] in order to analyse the performance of partial-width arrays in channels. More recently, however, Bonar et al [8] have shown that these coupled one-dimensional models may, under certain oscillatory flow conditions, neglect leading-order physics.…”
mentioning
confidence: 99%